Bulky and modular 3,3′-bipyrazoles as ligands: synthesis, characterization, and catalytic activity of Pd complexes - Spallek, Markus Jürgen; Stockinger, Skrollan Carina; Goddard, Richard; Rominger, Frank; Trapp, Oliver (European journal of inorganic chemistry, 2011)
In the present study, the properties of a new bidentate N,N′-chelating ligand class that bears an electron-excessive 3,3′-bipyrazole core have been investigated. The ligands are easily accessible in a three-step procedure by condensation with diethyl oxalate followed by tandem condensation with hydrazine hydrate and finally by aryl- or alkylation exclusively at the N-1,1′-pyrazole positions to furnish overall eleven new ligands with different electronic properties. After structural analysis of the ligands, their coordination to palladium, copper, and cobalt has been studied. These ligands coordinate the 2,2′-pyrazolyl nitrogen atoms in a bidentate fashion to the metals to realize complexes with an (L)MX2 motif. We present two crystal structures of Pd and Cu complexes, which to the best of our knowledge represent the first d8 and d9 2,2′-bipyrazole compounds coordinated through bidentate complexation. Initial catalytic experiments have been performed with palladium complexes with three bipyrazole ligands of this new class; the palladium-catalyzed copper-free Wacker oxidation of different alkenes showed superior activity compared to 2,2′-bipyridines. We attribute this to a higher redox potential of the 3,3′-bipyrazoles, which are ― besides electronic effects ― also strongly influenced by steric effects. These might be enforced by the extended ligand backbone, the choice of the wingtip substitution, and the smaller coordination cavity within the N2,N2′ atoms compared to 2,2′-bipyridine ligands.